Toxicity of different biodiesel exhausts in primary human airway epithelial cells grown at air-liquid interface - Landwehr, K.R.; Hillas, J.; Mead-Hunter, Ryan; King, A.; O'Leary, R.A.; Kicic, Anthony; Mullins, Ben; Larcombe, Alexander (ELSEVIER, 2022)
Biodiesel is created through the transesterification of fats/oils and its usage is increasing worldwide as global warming concerns increase. Biodiesel fuel properties change depending on the feedstock used to create it. The aim of this study was to assess the different toxicological properties of biodiesel exhausts created from different feedstocks using a complex 3D air-liquid interface (ALI) model that mimics the human airway. Primary human airway epithelial cells were grown at ALI until full differentiation was achieved. Cells were then exposed to 1/20 diluted exhaust from an engine running on Diesel (ULSD), pure or 20% blended Canola biodiesel and pure or 20% blended Tallow biodiesel, or Air for control. Exhaust was analysed for various physio-chemical properties and 24-h after exposure, ALI cultures were assessed for permeability, protein release and mediator response. All measured exhaust components were within industry safety standards. ULSD contained the highest concentrations of various combustion gases. We found no differences in terms of particle characteristics for any of the tested exhausts, likely due to the high dilution used. Exposure to Tallow B100 and B20 induced increased permeability in the ALI culture and the greatest increase in mediator response in both the apical and basal compartments. In contrast, Canola B100 and B20 did not impact permeability and induced the smallest mediator response. All exhausts but Canola B20 induced increased protein release, indicating epithelial damage. Despite the concentrations of all exhausts used in this study meeting industry safety regulations, we found significant toxic effects. Tallow biodiesel was found to be the most toxic of the tested fuels and Canola the least, both for blended and pure biodiesel fuels. This suggests that the feedstock biodiesel is made from is crucial for the resulting health effects of exhaust exposure, even when not comprising the majority of fuel composition.